Enhancing Learning Readiness and Interest of Special Education Students by Using Recreational Therapeutic Activities through Observation Methods - Mohd Izzat Syafiq Ramlan; Mohd Mokhtar Tahar; Norhidayah Abu Yamin; Juwaidah Rani (Department of Special Education, 2018)
Learning readiness and interest is an important element that has become an indicator for success in the learning process for special education students. Therefore, this research is conducted to study the effectiveness of Recreational Therapeutic Activities as an alternative method to enhance learning readiness and interest for special education students. Five special education students with learning problems and five teachers were chosen at a school in Tampin District, Negeri Sembilan, Malaysia. This research was conducted with action research using a qualitative approach which adapted the Honet & Mumford cycle model and the Herman Witkins Model. The data collection method is observation checklist adapted from The Taylor Academic Problem Indentification Checklist. Data were collected for 8 weeks in two cycles to see the effects of therapeutic recreational towards cognitive, emotional and social domains. The data were analyzed and explained qualitatively by theme. The findings show that the effects of recreational therapeutic activities can enhance the readiness and interest in learning of special education students with learning problems in the aspects of cognitive, emotional and social domains. The most dominant domains are cognitive and emotional domains. The findings of this research can be used as a guideline by special education teachers to enhance learning readiness and interest of special education students.